Celebrex in treatment of joint diseases in patients with risk factors of gastropathy and cardiovascular palhalodydevelopment - N. V. Chichasova; G R Imametdinova; E L Nassonov (Научно-практическая ревматология)
Literature digest is presented concerning to gastrointestinal and cardiovascular safety of selective COX- 2 inhibitors including results of Russian clinico-endoscopic study of celebrex efficacy and tolerability in osteoarthritis (OA). Celebrex was administered to the pts with risk factors of gastrointestinal and cardiovascular adverse events development. Results of longstanding treatment of pts with OA and rheumatoid arthritis (RA) which were prospectively followed up are presented. Celebrex was shown to have high efficacy (about 90% responders) and good tolerability independently on age, duration of treatment and daily dose. Esophagogastroduodenoscopy revealed ulcer development in 4% pts with OA with history of ulcer and in 2,4% pts with RA.